2021
DOI: 10.1038/s41531-021-00165-y
|View full text |Cite
|
Sign up to set email alerts
|

Weeding through the haze: a survey on cannabis use among people living with Parkinson’s disease in the US

Abstract: Symptomatic management of Parkinson’s disease (PD) is complex and many symptoms, especially non-motor symptoms, are not effectively addressed with current medications. In the US, cannabis has become more widely available for medical and recreational use, permitting those in the PD community to try alternative means of symptom control. However, little is known about the attitudes towards, and experiences with, cannabis use among those living with PD. To address this shortcoming, we distributed an anonymous surv… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(31 citation statements)
references
References 31 publications
2
18
0
Order By: Relevance
“…Another area that cannabis may have a benefit is on the alleviation of non-motor symptoms. One randomized study [36] A similar outcome was observed in a US survey [40].…”
Section: Discussionsupporting
confidence: 56%
See 4 more Smart Citations
“…Another area that cannabis may have a benefit is on the alleviation of non-motor symptoms. One randomized study [36] A similar outcome was observed in a US survey [40].…”
Section: Discussionsupporting
confidence: 56%
“…Also, from a telephone survey of 39 PD patients taking medicinal cannabis approved by the Ministry of Health in Israel, 59% reported decrease in tremor symptoms [43] single CBD administration reduced anxiety in PD in sleep disorders after taking cannabis. 46%, 31%, and 15% respondents reported considerable, moderate, and slight improvement in sleep disorders with only 9% who did not [40].…”
Section: U N C O R R E C T E D a U T H O R P R O O Fmentioning
confidence: 97%
See 3 more Smart Citations